Las biotecnologías entre ética y derecho - Velazquez, Lourdes (Studia Bioethica, 2016)
Is a reflection on the current world from the perspective of Bioethics and Law, taking into account the importance of an ethical approach considering the commodification of human life several new technology-related developments, and value crisis of our times, emphasizing on the need for a humanistic approach to address them.